CURRENT SURGICAL STRATEGIES AND RISK-BASED CLASSIFICATION IN VENTRAL HERNIA REPAIR - Karimov Kh.Ya.; Ibrokhimov M.Yo.; Eshonkulova B.D.; Shukurov B.I. (Central Asian Journal of Medicine, 2025)
Ventral hernias are among the most common conditions in abdominal surgery, associated with high rates of postoperative complications and recurrences. This review summarizes contemporary insights into the pathogenesis, classifications of ventral hernias (EHS, VHWG, HPW, CeDAR), approaches to assessing loss of domain, and patient risk stratification. Modern principles of surgical decision-making are discussed, including the use of various mesh implant positions and materials, as well as the importance of preoperative optimization of modifiable risk factors. Particular emphasis is placed on the advances in minimally invasive and robotic techniques, which represent the most promising directions for improving outcomes in ventral hernia repair.